Revisiting the minimal universal extra dimensions with mass-dimension-five operators. (1st March 2021) - Dias, M.; Duarte, Laura; de Campos, F.
Abstract: We examine a minimally modified version of the minimal universal extra dimension, using electric and magnetic dipole moments and Higgs portals operators to describe new interactions between fermionic dark matter and Standard Model particles. We assume the dark matter in the form of weakly interacting massive particle (WIMP). This suggests that the four-dimensional D theory is naturally suppressed by the size of the extra dimension R, without adding new free parameters to the model. We show the LHC potential to discover the fermionic WIMP considering the mono-jet + channel, highlighting the existence of a viable mass range and compactification scale, , in this new scenario. Using ATLAS data for this channel, corresponding to an integrated luminosity of in the analysis, we found a lower bound for . We identify that for a compactification scale of, our fermionic particle is a viable candidate to a dark matter constituent which has been shown to be compatible with relic abundance measurements from the Planck Collaboration.